PEMBELAJARAN FISIKA MELALUI TIPE STAD DAN JIGSAW II DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS DAN ORIENTASI KEPRIBADIAN SISWA - Laxmi Zahara (Educatio, 2012)
This research uses experimental methods. Its population was all of the students in the first semester of MA Muallimat NW Pancor Nusa Tenggara Barat in the academic year 2010/2011. The samples was taken using cluster random sampling, consisted of two classes, the class X-1 were treated using type of learning STAD and classes X-3 were treated using type of learning 2nd Jigsaw. The data was collected using tes studentâ€™s achievement, and questionnaire for critical thinking ability and orientation of collaborativepersonality. The hypotheses of the research were tasted by using a three-way analysisof variance (ANOVA) with unequal cells aided by the computer software minitab 15. Then, they were tasted by using the Main effects plot formulae.Base on the result of the analysis, conclusions were drawn as follows. 1) there was an effect of the use cooperative learning type STAD and 2nd Jigsaw toward studentâ€™s achievement, (2) There was no effect of the critical thinking ability toward student achievement, (3) There was no effect of the orientation of collaboratve personality toward studentâ€™s achievement, 4) There was no interaction between cooperative learning and studentâ€™s critical thinking ability toward student achievement, 5) There was an interaction between cooperative learning and the studentâ€™s orientation of collaborative personality toward studentâ€™s achievement, 6) There was no interaction between the studentâ€™s critical thinking ability and orientation of collaborative personality, 7) There was no interaction between cooperative learning, the critical thinking ability, and  orientation of collaborative personallity toward studentâ€™s achievement. Key words: STAD, 2nd Jigsaw, critical thinking ability, orientation of collaborative personallity, Kinematics of linier Motion, and studentâ€™s achievement.